2008
DOI: 10.1002/chem.200800804
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Transition Metal–Phosphorus Triple Bonds towards Triply Bonded [{CpMo(CO)2}2]: Formation of Heteronuclear Cluster Compounds

Abstract: Thermolysis of [Cp*P{W(CO)5}2] (1) in the presence of [{CpMo(CO)2}2] leads to the novel complexes [{(CO)2Cp*W}{CpMo(CO)2}(micro,eta2:eta1:eta1-P2{W(CO)5}2)] (6; Cp=eta5-C5H5, Cp*=eta5-C5Me5), [{(micro-O)(CpMoWCp*)W(CO)4}{micro3-PW(CO)5}2] (7), [{CpMo(CO)2}2{Cp*W(CO)2}{micro3-PW(CO)5}] (8) and [{CpMo(CO)2}2{Cp*W(CO)2}(micro3-P)] (9). The structural framework of the main products 8 and 9 can be described as a tetrahedral Mo2WP unit that is formed by a cyclisation reaction of [{CpMo(CO)2}2] with an [Cp*(CO)2W[tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
1
25
0
4
Order By: Relevance
“…In addition, the found formation process of triphosphines is completely different from those of former reports on hydrogenation of halogen-containing triphosphines, methanolysis of silylated triphosphines, and the catalytic dehydrocoupling of phosphines. [25] This reaction pattern of the pentelidene complexes 1 is in strong contrast to the Cp* migration process of 1 usually found to form the triply bonded intermediates [Cp*(CO) 2 WE!W(CO) 5 ], [26] which can be trapped by alkynes, [27] phosphaalkynes, [28] and compounds with metalmetal multiple bonds [29] to form transition-metal cages containing Group 15 elements. Moreover, under photolytic conditions, a radical Cp* displacement is found.…”
Section: Methodsmentioning
confidence: 88%
“…In addition, the found formation process of triphosphines is completely different from those of former reports on hydrogenation of halogen-containing triphosphines, methanolysis of silylated triphosphines, and the catalytic dehydrocoupling of phosphines. [25] This reaction pattern of the pentelidene complexes 1 is in strong contrast to the Cp* migration process of 1 usually found to form the triply bonded intermediates [Cp*(CO) 2 WE!W(CO) 5 ], [26] which can be trapped by alkynes, [27] phosphaalkynes, [28] and compounds with metalmetal multiple bonds [29] to form transition-metal cages containing Group 15 elements. Moreover, under photolytic conditions, a radical Cp* displacement is found.…”
Section: Methodsmentioning
confidence: 88%
“…The anionic ligand is trapped with iron(II) chloride with formation of the respective ferrocene derivative. [35] One molybdenum example has been published by Scheer et al [36] In many cases, these complexes were prepared by reaction of the dianionic ligand system with a suitable complexation reagent.While the reaction of a lithiated primary or secondary phosphane with a fulvene affords a ligand system with one carbon atom between the cyclopentadienyl and the phosphane moieties, [15,30,37] the corresponding reactions with spiro[2.4]hepta-4,6-dienes give rise to ligand systems with an ethylene bridge between them. Deprotonation, reaction with spiro[2.4]hepta-4,6diene, followed by treatment with nickel dihalide complexes www.eurjic.org FULL PAPER 1989; [9] 2 bears an internal amine ligand and was prepared by Hadjiliadis et al in 1998; [10] 3 represents a cyclopentadienylalkylphosphane nickel chelate and was prepared in our group in 2007; [11] 4 is a cationic chelate with sulfur coordination, which was prepared by Rauchfuss et al in 1985, [12] and alkene complex 5 was prepared by Okuda et al.…”
mentioning
confidence: 99%
“…This reaction proceeds primarily under thermolytic conditions, however, photolysis of 1 leads, additionally, to the elimination of a Cp*C moiety and the formation of the radical intermediate H. [24] The electronic structure of H was recently calculated by using DFT methods. [21] We now find that this intermediate acts as a phosphorus-radical-transfer reagent and is responsible for the reaction of 1 with diphosphenes to afford an unprecedented complex of type E.…”
mentioning
confidence: 97%
“…[18] We have shown that the phosphinidene complex [Cp*P{W(CO) 5 } 2 ] (1) [19] is an excellent starting material for the in situ generation of intermediate G, [20] which contains a tungsten-phosphorus triple bond (Scheme 1). The intermediate can be trapped by organometallic compounds that contain multiple metal-metal bonds, [21] alkynes, [22] and phosphaalkynes to give novel clusters, metal-containing heterocycles, or cage compounds. In the latter reaction, an unusual opening of the Cp* ligand is observed to form an unprecedented 1,2-diphosphacyclooctatetraene ligand.…”
mentioning
confidence: 99%